Kemampuan berpikir kritis materi hak dan kewajiban pada pembelajaran pendidikan kewarganegaran peserta didik kelas IV sekolah dasar - Diah Hayu Novita Sari; Hasan Mahfud; Dwi Yuniasih Saputri (Didaktika Dwija Indria, 2021)
Abstract. This research to describe the critical thinking skills of students on the material rights and obligations of the civic education learning class IV Tegalrejo Public Elementary School No. 98 academic years 2020/2021. Critical thinking was important to face the competition of life in the 21st century. This qualitative research used descriptive qualitative and phenomenological approache. This study recommends other research on critical thinking skills. Teachers and students of grade IV Tegalrejo Public Elementary School No.98, totaling 22 students, became the research subjects. The researcher used observation, interviews, and documentation to collect the data. The data analysis technique of this research based on the interactive analysis technique of Miles and Huberman. Data validity test by triangulation. Based on the results of the study it can be concluded that the critical thinking skills of students in the material of rights and obligations in the civic education learning class IV Tegalrejo Public Elementary School  No. 98 Academic Year 2020/2021 based on visible indicators was at a moderate level. This research expected to add knowledge for teacher, schools, and other researcher in developing critical thinking skills, especially in civic education learning so that it can optimize the knowledge and practice in everyday life.Keywords: critical thinking, rights and obligations, civic education, primary school .